Eccentric overload training: A viable strategy to enhance muscle hypertrophy? - Schoenfeld, B. J.; Grgic, J. (Strength and Conditioning Journal, 2018)
It has been postulated that eccentric actions have the greatest effect on muscle hypertrophy. The potential hypertrophic benefits to eccentric training raise the possibility that muscular growth could be enhanced by supplementing resistance training with eccentric overload training. In this article, we examine whether this strategy is efficacious for enhancing muscle growth.